Cyclical hematuria-ureteral endometriosis: a case report - Ravula, Sindura Ganga; Shetty, Harish; Rajesh, Aparna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Little attention has been paid for the renal involvement in endometriosis, a rare and silent disorder which ultimately lead to renal failure. Involvement most commonly may be limited to single ureter (left one) and it is usually involvement extrinsically. Although cases have been reported in the literature, true incidence of ureteral involvement is still not known. The diagnosis is difficult as the disease has non-specific symptoms. Only high index of suspicion with radiological support would be helpful in early diagnosis. Early cases may be benefited with progestin or Anti-aromatase therapy, most cases need surgery, either laparoscopically or laparotomy.